Perkembangan Ilmu Kaligrafi Pada Masa Pra-Islam - Arjuna Dwi Maulana (Jurnal Shaf, 2024)
The science of calligraphy appeared in pre-Islamic times, because of the writings around the walls of the Kaaba called Al-Mu'allaqat. However, at that time the Arabs preferred their minds and memories to remember something rather than write. This research uses literature study, in which the researcher takes references from several books and journals related to research. The results of this study show that, in pre-Islamic times, the science of calligraphy was not of interest to the Arabs. However, after the arrival of Islam, calligraphy became one of the Islamic arts. Because the science of calligraphy has a very big influence on the writing of the Qur'an. Until now there are many calligraphy sciences that have developed greatly such as Tsulus, Naskhi, Diwani, Rayhani, Pharisees, Diwani Jali, Kufi, Riq'a